2019
DOI: 10.3389/fbloc.2019.00003
|View full text |Cite
|
Sign up to set email alerts
|

Toward More Rigorous Blockchain Research: Recommendations for Writing Blockchain Case Studies

Abstract: About a decade ago the fundamental operating principle of the Blockchain was introduced. It took several years before the technology gained widespread recognition in industry and academic communities outside of the computer science sphere. Since then many academic communities have taken up the topic, but so far no well-defined research agenda has emerged: research topics are scattered and rigorous approaches are scarce. More often than not, use cases implemented by industry apply a trial and error approach and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 59 publications
0
60
0
Order By: Relevance
“…This paper follows a case study research design that lies between and takes insight from both gaps and holes (GAH), and social construction of reality (SCR) research designs as recently defined by Treiblmaier (2019) in this journal. First, following the GAH research design, correspondent banking and payment infrastructures were identified as the paramount gap in the existing literature on remittances.…”
Section: Methodsmentioning
confidence: 99%
“…This paper follows a case study research design that lies between and takes insight from both gaps and holes (GAH), and social construction of reality (SCR) research designs as recently defined by Treiblmaier (2019) in this journal. First, following the GAH research design, correspondent banking and payment infrastructures were identified as the paramount gap in the existing literature on remittances.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it was our goal to highlight the potentials of blockchain in marketing, but we also need to mention potential challenges that might emerge from the (inter-)organizational integration of blockchain technology. Blockchains are not silver bullets or a panacea for all contemporary marketing issues but rather exhibit several shortcomings and potential negative consequences (Treiblmaier, 2019b). Compared to conventional databases, blockchain technology has several downsides.…”
Section: Conclusion and Limitationsmentioning
confidence: 99%
“…This decentralized methodology would wipe out single points of failure, making a stronger ecosystem system for devices to run on. The record is tamper-proof and cannot be controlled by noxious actors since it doesn"t exist in any single area, and what's more, man-in-the-middle attacks can't be organized since there's no single string of communication that can be catching [51]. In an IoT system, the blockchain can keep a changeless record of the historical backdrop of smart devices.…”
Section: Why Blockchain Technologymentioning
confidence: 99%